ANALISIS PENGARUH MONEY LAUNDRY TERHADAP PROFIT MARGIN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2010-2014 - Agnes Susana Merry Purwati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
During the development of the world economy with a wide range of advanced technologies,many cases of money laundry in Indonesia is quite a significant impact to the traffic balance ofpayments. Money Laundry will affect profit or profit is the ultimate goal to be achieved a company's mostimportant profit or maximum profit. By obtaining the maximum profit the company will achieve thetargets that have been targeted. This is the reason for doing research on the Indonesian StockExchange (BEI) branch of Bandar Lampung.The purpose of this study was conducted to analyze the effect of money laundry to the profitmargin of the banking company. The analysis performed in this study is the analysis of quantitativedescriptions by analyzing the development of the level of assets, liabilities, revenues, and earnings, ratioanalysis ROA, ROE and NPM as well as analysis of the calculation of money landry with the formula setforth by the Financial Services Authority (FSA) which will in an analysis to see the effect of moneylaundry to the profit margin.